2014
DOI: 10.1002/jbm.b.33325
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun poly(ε‐caprolactone)‐based skin substitutes: In vivo evaluation of wound healing and the mechanism of cell proliferation

Abstract: In the present study, we have fabricated electrospun poly(ε-caprolactone)-based membranes, characterized and studied the in vivo cell migration and proliferation and wound healing activity. Moreover, we did not seed any cells prior to the animal implantation and we could observe excellent fibroblast attachment and cell proliferation. Further full thickness excision wound on guinea pig completely healed within 35 days. We could reach in an assumption that the enhanced cell proliferation and wound healing might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 60 publications
1
37
0
3
Order By: Relevance
“…The surface morphologies of the fabricated are affected by several factors such as nature of the solvent, concentration, and viscosity of the solution, distance, charge density and applied voltage. [18][19][20] The fabricated scaffolds have smooth morphology without noticeable beads and thinner diameter was observed in PC scaffolds as compared to pure PCL scaffolds. A similar result was also observed by Shi et al in the presence of CNCs with the poly(lactic acid) polymer matrix.…”
Section: Morphology Of Cncsmentioning
confidence: 90%
See 1 more Smart Citation
“…The surface morphologies of the fabricated are affected by several factors such as nature of the solvent, concentration, and viscosity of the solution, distance, charge density and applied voltage. [18][19][20] The fabricated scaffolds have smooth morphology without noticeable beads and thinner diameter was observed in PC scaffolds as compared to pure PCL scaffolds. A similar result was also observed by Shi et al in the presence of CNCs with the poly(lactic acid) polymer matrix.…”
Section: Morphology Of Cncsmentioning
confidence: 90%
“…14 Polymer/CNCs composites have been studied from the last several decades in tissue engineering applications. [15][16][17][18][19][20][21][22][23][24] Besides, it has been found that the external stimuli including the electrical eld have wide effects on cell proliferation in the presence of CNCs. 25 It was observed that CNCs have low electroactive materials, and this property can be tuned by using highly conductive materials such as graphene or carbon nanotube with CNCs.…”
Section: Introductionmentioning
confidence: 99%
“…7 Although many biomaterials are widely used in tissue engineering, such as PLA and PCL, cell compatibility is essential for the selection of bioink for cell encapsulation and bioprinting. 35 For instance, PLA with a relatively high processing (melting) temperature is not suitable for bioprinting. 6 Based on this and previous studies, hydrogels 36 ; natural biopolymers such as alginate, chitosan, gelatin, etc.…”
Section: Bioinkmentioning
confidence: 99%
“…In another aspect of regenerative medicine, wound healing, electrospinning is now an established technique for the production of wound dressings for the treatment of chronic wounds [6,[29][30][31][32][33][34][35]. Many modern wound dressings are no longer only a barrier to protect a wound from infection but they are also expected to enhance the healing of the wound [36].…”
Section: Application and Importance Of Electrospun Nanofibrous Materialsmentioning
confidence: 99%